Developing A Mathematics Learning Media to Explain Formula Of Area of Kite Using Hawgent - Pereira, Jerito; Tan, Shiwei; Li, Li; Purnama, Aditya (Indonesian Journal of Science and Mathematics Education, 2020)
This study aims to develop Hawgent Dynamic Mathematics Software Learning Media. The broad material of ICT-based kites as a medium for learning mathematics for grade IV SD students. The research method used in this research is Research and Development (R and D) with a 4-D model. The results of the material expert’s assessment of the six components include: the language aspect is 70%, the ease of use of learning media reaches the highest average of 90%, and it is concluded that the overall average percentage is 83.33%. It can be said that the ICT-based learning media that have been designed are in the feasible category. While the results of the material expert’s assessment of the four aspects obtained an average percentage of 87.89%. Based on the results of the study Hawgent Dynamic Mathematics Software Learning Media can be used as a learning media for learning mathematics to find the area ofa kite.